A Numerical Analysis of Ground Vibration Induced by Typical Rail Corrugation of Underground Subway - Mengting Xing; Caiyou Zhao; Ping Wang; Ju Lu; Qiang Yi (Shock and Vibration)
A two-step approach is used to establish a numerical prediction model to study the impact of typical rail corrugation on ground vibration from an underground subway. In the first step, a vehicle-track-tunnel rigid-flexible coupling subsystem is established based on a lumped mass model dynamics and finite element analysis cosimulation method to simulate the generation of vibration. In the second step, a track-tunnel-soil three-dimensional (3D) finite element subsystem is built to simulate the propagation of the vibration. The ground vibration response is obtained by applying the wheel-rail force calculated from the first step. A section of Chengdu Metro Line 3 is studied, and the accuracy of the numerical prediction model is then verified by comparison with in-situ measurement. Based on that, the impact of corrugation on wheel-rail interaction and ground vibration is investigated by taking rail corrugation in typical subway sections and track geometry irregularities as system input excitation. In addition, to further analyze the sensitivity between different wavelength components in the rail corrugation samples and ground vibration, the measured rail corrugation is decomposed into five kinds with different wavelength components by filtering. The results show that the typical rail corrugation has a large impact on ground vibration response, which increases significantly in the range 8–16 Hz and 50–80 Hz, and the impact decreases with the distance from the vibration source. For typical subway rail corrugation with the significant wavelength of 125 mm and the secondary significant wavelength of 63 mm, the ground vibration response is sensitive to two wavelength components at 40–60 mm and 60–100 mm. Rail corrugation with the short wavelength of 60–100 mm significantly affects ground vibration levels.